Problems of using rockroses in Tuber melanosporum culture: soil and truffle harvest associated with Cistus laurifolius - Garcia-Montero, L. G.; Pascual, C.; García-Abril, A.; García-Cañete, J. (Agroforestry Systems, 2007)
The Pe´rigord black trufﬂe (Tuber melanosporum Vittad.) can mycorrhize with rockroses (Cistus L.) in Mediterranean forests. These shrubs may be of interest for trufﬂe cultivation as they produce early carpophores, collaborate in tree mycorrhization and in the survival of Tuber melanosporummycelium. However, there are very few quantitative studies on trufﬂe production associated with Cistus. For this reason, we have carried out a study on the natural production of Tuber melanosporum associated with Cistus laurifolius L. in central Spain. An Anova test conﬁrmed the existence of signiﬁcant differences in carpophore production in four habitats, with and without the presence of C. laurifolius. Twenty-one burns associated with C. laurifolius showed less signiﬁcant production than the rest. We also conﬁrmed that in 122 burns, Tuber melanosporum was always unequivocally associated with the root base of Quercus L. or Corylus L. trees. Similarly, ﬁve trufﬂe-collectors conﬁrmed that they had never found a single burn with carpophore production associated exclusively with rockroses. It has also been statistically veriﬁed that many Cistus die in Tuber melanosporum burns, whereas in old burns with minimum carpophore production, a new colonization of young Cistus has been observed. This study also conﬁrms that C. laurifolius mycorrhizes easily with Tuber melanosporum. We propose that Cistus laurifolius may act as transmitters of Tuber melanosporum, although they do not induce fruiting. Consequently, the commercial cultivation of Cistus laurifolius mycorrhized with Tuber melanosporum for production is not recommended in trufﬂe culture. The results reported substantiate the negative observations in cultivations ofT. melanosporum with other Cistusspecies.
Keywords: host plants; Mediterranean forests; Mushroom production; Mycorrhizal fungi; Woodland products